Scaling Features of High‐Latitude Geomagnetic Field Fluctuations at Swarm Altitude: Impact of IMF Orientation. Issue 10 (14th October 2017) - De Michelis, Paola; Consolini, Giuseppe; Tozzi, Roberta; Marcucci, Maria Federica
Abstract: This paper attempts to explore the statistical scaling features of high‐latitude geomagnetic field fluctuations at Swarm altitude. Data for this study are low‐resolution (1 Hz) magnetic data recorded by the vector field magnetometer on board Swarm A satellite over 1 year (from 15 April 2014 to 15 April 2015). The first‐ and second‐order structure function scaling exponents and the degree of intermittency of the fluctuations of the intensity of the horizontal component of the magnetic field at high northern latitudes have been evaluated for different interplanetary magnetic field orientations in the GSM Y ‐ Z plane and seasons. In the case of the first‐order structure function scaling exponent, a comparison between the average spatial distributions of the obtained values and the statistical convection patterns obtained using a Super Dual Auroral Radar Network dynamic model (CS10 model) has been also considered. The obtained results support the idea that the knowledge of the scaling features of the geomagnetic field fluctuations can help in the characterization of the different ionospheric turbulence regimes of the medium crossed by Swarm A satellite. This study shows that different turbulent regimes of the geomagnetic field fluctuations exist in the regions characterized by a double‐cell convection pattern and in those regions near the border of the convective structures. Key Points: Investigation of scaling features of magnetic spatiotemporal fluctuations at Swarm's altitude Change of the geomagnetic fluctuation scaling properties with IMF conditions Characterization of ionospheric high‐latitude turbulence